Assessing local knowledge on the diversity and abundance of bushmeat species and hunting pressure in the fragmented forest islands of southern Benin (Dahomey Gap). (25th March 2022) - Djagoun, Chabi A. M. S.; Nago, Gilles; Azihou, Akomian F.; Vodouhê, Fifanou; Agli, Auriane; Zanvo, Stanislas; Djossa, Bruno; Assogbadjo, Achile; Sinsin, Brice; Gaubert, Philippe
Abstract: Illegal hunting of wildlife is one of the major issues in tropical ecosystems, especially when it occurs in highly degraded habitats with forest cover fragmentation. In this study, we assessed the impact of bushmeat hunting in a large forest patch (the Lama Natural Forest; LNF) and 11 nearby forest islands, using Traditional Ecological Knowledge from 240 interviewees across 16 villages. Thirty‐five species belonging to nine orders of mammals, birds and reptiles were mentioned by local communities. Rodentia were significantly more observed in the forest islands, whereas medium‐sized mammals belonging to Carnivora, Primates, Artiodactyla, Pholidota and Hyracoida were found predominantly in LNF. Approximately 57% of the species were reported to be rare in the forest islands, whereas c. 77% were listed as abundant in LNF, confirming the role of LNF as a refuge for forest species targeted by the bushmeat trade. Generalised linear models indicated that species sighting frequencies were positively correlated with perimeters of forest patches. We found hunting pressure to be greater in forest islands in the vicinity of LNF than those further away. Our results suggest that long‐term conservation of wildlife in southern Benin may require a 'mainland‐islands' approach including both LNF and its surrounding forest islands. Résumé: La chasse illégale de la faune sauvage est l'un des problèmes majeurs des écosystèmes tropicaux, surtout lorsqu'elle se produit dans des habitats fortement dégradés avec une fragmentation du couvert forestier. Dans cette étude, nous avons évalué l'impact de la chasse de viande de brousse sur une grande aire forestière (la Forêt Naturelle de la Lama; FNL) entourée de 11 îlots forestiers, en utilisant les connaissances écologiques traditionnelles de 240 personnes interrogées dans 16 villages. Trente‐cinq (35) espèces appartenant à neuf ordres de mammifères, d'oiseaux et de reptiles ont été mentionnées par les communautés locales. Les rongeurs ont été significativement plus observés dans les îlots forestiers, tandis que les mammifères de taille moyenne appartenant à l'ordre des Carnivores, Primates, Artiodactyles, Pholidotes et Hyracoïdes ont été trouvés principalement dans la FNL. Environ 57% des espèces ont été signalées comme étant rares dans les îlots forestiers, alors que 77% d'entre elles ont été répertoriées comme étant abondantes dans la FNL, ce qui confirme le rôle de cette dernière en tant que refuge pour les espèces forestières ciblées par le commerce de viande de brousse. L'analyse des modèles linéaires généralisés a indiqué que les fréquences d'observation des espèces étaient positivement corrélées avec les périmètres des forêt/îlots forestiers étudiés. Nous avons constaté que la pression de chasse était plus forte dans les îlots forestiers situés à proximité de la FNL que dans ceux qui en sont plus éloignés. Nos résultats suggèrent que la conservation à long terme de la faune sauvage dans le sud du Bénin pourrait nécessiter une approche "continent‐îles" intégrant à la fois la FNL et les îlots forestiers environnants.